Financial distress and business rescue: A Twenty-year scholarly literature review to direct future research - Ayaya, O. (Faculty of management and law international Conference (FMLIC), 2024)
This paper seeks to determine how much the business rescue (BR) discipline’s research has grown in the last two decades. In addition, it documents research gaps to provide directions for future research. Scholars have contributed to organisational change theory, including turnaround management and business rescue. The business rescue topic has interested scholars since 2004 when the Department of Trade, Industry, and Competition (DoTIC) initiated South Africa’s corporate law reforms that saw the promulgation of the Companies Act (Act No. 71 of 2008). The investigation explores BR literature using this systematic literature review and bibliometric analysis. The business rescue literature comprised 133 postgraduate (master and doctoral) theses from Google Scholar (GS) and 31 journal articles indexed by the Web of Science (WoS). The researcher had license restrictions on the use of the Scopus database. The results of the reviews around the business rescue are synthesised in the context of organisation change theory. The numerous features of corporate rehabilitation that form part of business rescue were grouped thematically to respond to review questions. BR research reflects the development stage of the discipline. Much time has been spent discerning the appropriateness of Chapter 6 of the Companies Act to Southern Africa. The BR issues addressed BR aspects such as contents, context, and processes. A limited number of theses have been converted to the WoS-indexed journal articles. Law and business management scholars have driven the research agenda with negligible contributions from economists and accountants. International comparisons are also limited. The study fosters an agenda for future research based on aggregating BR disciplinary research issues to highlight current gaps and offer potential research questions. The review contributes to understanding BR as an occupational discipline worthy of professional pursuit and not just another management advisory service.
Journal article of FMLIC - Conference Proceedings 2024
Keywords: Bibliographic analysis; Business rescue; Financing; Professional; Regulation; Practices; Business; Financial statement